Acid rain - Davis, David R.F; Soare, Thomas F.
Learn how acid rain originated and witness its toll on the environment. Learn how this problem has escalated and they will consider what the ramifications will be if measures aren't taken to halt its progress. Discusses about the effects of acid rain.